ANALISIS WACANA KRITIS MODEL TEUN VAN DIJK PADA PEMBERITAAN KASUS KORUPSI EKSPOR BENIH LOBSTER DALAM BERITA DARING (CRITICAL DISCOURSE ANALYSIS OF VAN DIJK MODEL ON THE NEWS OF LOBSTER SEED EXPORT CORRUPTION CASE IN DARING NEWS) - Ayu Humairoh Hakim; Sulis Triyono (Metalingua: Jurnal Penelitian Bahasa, 2021)
his article discusses the van dijk’s analysis on daring news lobster seed export corruption cases. The aim of this study is to analyze, and describe how the text structures, social cognition and social context as the elements of van Dijk’s analysis in analyzing daring news. This study using a qualitative descriptive research method, the type of research is library research. Then this study is a qualitative approach and critical discourse analysis approach is Teun A. van Dijk model. The subjects of this study were daring news namely Tempo.co, Tirto.id and BBC News, which were published November 26 to 30-2020 according to the incident. The results showed that from the three news reports meet the level of discourse analysis using van Dijk model, namely text structure (macro structure, superstructure, and micro structure), after that the element of social cognition and social context of the corruption case became one of the bed social phenomena, because it does not reflect a good personal example.